If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 + -6x = 21x + 90 Reorder the terms: 61 + -6x = 90 + 21x Solving 61 + -6x = 90 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 61 + -6x + -21x = 90 + 21x + -21x Combine like terms: -6x + -21x = -27x 61 + -27x = 90 + 21x + -21x Combine like terms: 21x + -21x = 0 61 + -27x = 90 + 0 61 + -27x = 90 Add '-61' to each side of the equation. 61 + -61 + -27x = 90 + -61 Combine like terms: 61 + -61 = 0 0 + -27x = 90 + -61 -27x = 90 + -61 Combine like terms: 90 + -61 = 29 -27x = 29 Divide each side by '-27'. x = -1.074074074 Simplifying x = -1.074074074
| 2x+11x+5=0 | | y+3=4+3x | | (w+18)(w-21)=0 | | 3y^2-7y=0 | | 9-8x=75-29x | | 15x-24x=216 | | 5x-4y=y+3 | | m+8-5=3 | | 7(7n+4)(n+3)=0 | | 5x+10=-125-10x | | 5x+13=-17-9x | | 3(4+1)-4= | | Y^2+2y-3=0 | | 5x+x=x+13 | | (13b-2)-4(3b+4)=-3 | | 374=18c+4c | | 5u-4=-19 | | x+x+1=171 | | x-6y=9 | | x+x+x+1=171 | | .4x-.35x=2 | | 3x-5=5x-15 | | x+x+4=38 | | 9(5d-7)= | | 7x-y=-2 | | -3e+=-23 | | (2x+5)(3x-7)=0 | | 3x+7(x+2)-13=12-3x | | 4(7c+4)= | | 3(x+2)=8+x | | -4(t-4)+6t=5t-1 | | 8x+4x+2+8=7x+3+4X |